Difficulties Faced by Mining Engineering Students When Translating English Idioms - Indri Lesta Siwidiani; Yusna Bantulu (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Idioms are fixed combinations of words whose meanings cannot be interpreted literally, making them difficult to translate without prior familiarity. This study aims to analyze the translation difficulties faced by mining engineering students in translating idiomatic expressions from English to Indonesian. This research employs a descriptive qualitative method. Data were collected through observation and note-taking techniques. The findings reveal that students encounter several challenges in the translation process. These include difficulties in identifying idioms, conveying equivalent meanings, selecting appropriate translation strategies, finding idioms with equivalent meanings, and locating idioms with equivalent structures and meanings. Among these, the greatest difficulty lies in identifying idioms. Out of a total population of 221 students, 61 students (approximately 27.6%) reported challenges in recognizing idiomatic expressions. Despite this, when students are familiar with certain idioms, they tend to translate them accurately and are even confident in using them in daily conversations. This suggests that familiarity with idiomatic expressions significantly influences translation accuracy. Therefore, it is essential to expose students to idiomatic expressions through various contexts and practices to improve their comprehension and translation skills. The study concludes that enhancing students’ exposure and understanding of idioms can reduce difficulties in translation and improve their overall translation competence.